2021
DOI: 10.1038/s41467-021-22992-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative cyclo-rearrangement of helicenes into chiral nanographenes

Abstract: Nanographenes are emerging as a distinctive class of functional materials for electronic and optical devices. It is of remarkable significance to enrich the precise synthetic chemistry for these molecules. Herein, we develop a facile strategy to recompose helicenes into chiral nanographenes through a unique oxidative cyclo-rearrangement reaction. Helicenes with 7~9 ortho-fused aromatic rings are firstly oxidized and cyclized, and subsequently rearranged into nanographenes with an unsymmetrical helicoid shape t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 44 publications
1
53
0
Order By: Relevance
“…Considering the tendency of [5]helicenes to undergo either light‐ or oxidant‐promoted cyclodehydrogenation resulting in the formation of planar products, we assumed that the appearance of the new signal in the HPLC data could be rationalized by a cyclization process [16–22] . We therefore turned to photostability studies of compound 1 using UV‐visible absorption spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the tendency of [5]helicenes to undergo either light‐ or oxidant‐promoted cyclodehydrogenation resulting in the formation of planar products, we assumed that the appearance of the new signal in the HPLC data could be rationalized by a cyclization process [16–22] . We therefore turned to photostability studies of compound 1 using UV‐visible absorption spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Helicenes possess multiple possibilities for structural expansion to adjust their properties, such as forming chiral nanographenes. 120 Indeed, there are a few examples of the application of helicenes in optoelectronic devices. In 2013, Campbell et al reported that an N-incorporating helicene formed well-ordered crystallized domains after annealing and behaved as a p-type material when employed in OFET.…”
Section: Device Applications Of Pah-based Semiconductorsmentioning
confidence: 99%
“…The application possibilities listed above have been discussed in this review. Particular attention is paid to nanographenes, including functionalized and heteroatoms-doped ones, which preparation and new applications constitute a “hot topic” in science and technology [ 6 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Currently, only bottom-up methods, where nanographene is constructed from smaller entities by stepwise organic synthesis, allow the preparation of nanographenes, including functionalized and doped ones, with perfect control of shapes and sizes and, therefore, perfectly defined properties [ 2 , 5 , 6 , 11 , 12 ,…”
Section: Introductionmentioning
confidence: 99%
“…It should be added that nanographenes (graphenoids), obtained via reactions discussed in this review, can be planar or otherwise distorted, that is, non-planar, one- (1D), two- (2D), and three-dimensional (3D) [ 6 , 11 , 12 , 17 , 23 , 24 , 25 , 26 , 36 , 38 , 40 , 43 , 46 , 47 , 49 , 52 ]. Graphenoids with planar sheets of varying size, shape, and periphery have made great progress in practical applications of electronics, energy storage, catalysis, and biosensing [ 6 , 11 , 12 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 47 , 50 , 52 , 53 ]. In recent years, a growing number of graphenoid studies have focused on unusual curved and warped stru...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation